Effect of Nitrophoska® and irrigation interval on root and sugar yield of sugar beet (Beta vulgaris L.), Gezira State, Sudan - Mohammed, Shamseldin A.; Gangi, Ali S.; Mohamed, Ibrahim E. (Gezira Journal of Agricultural Science; Vol 18 No 1 (2020), 2020)
Sugar beet is one of the promising crops in the Sudan due to its high root, sugar yield and by-products as an industrial crop. The crop is also a promising alternative energy crop for the production of ethanol. An experiment was conducted at the experimental Farm of the Faculty of Agricultural Sciences, University of Gezira, Wad Medani, Sudan, during seasons 2012/13 and 2013/14. The objective was to investigate the effects of irrigation intervals (7, 14 and 21 days) and Nitrophoska (NPK compound fertilizer) rates (0, 100, 150 and 200 kg/ha) on root and sugar yield of sugar beet (Ballade cultivar) under Gezira conditions. Split-plot design with three replicates was used. Irrigation intervals were allotted to the main plots and Nitrophoska rates to the subplots. Results showed that shortening irrigation intervals from 21 to 14 and 7 days increased root diameter, root weight and root and sugar yields in both seasons. In addition, Nitrophoska rate of 150 kg/ha substantially improved most of the studied root characters and sugar yield in both seasons. Depending on the results of this study, to obtain high root and sugar yields from sugar beet Ballade cultivar, it could be recommended  to apply 150 kg/ha of  Nitrophoska  and  irrigate every 7 to14 days.   بنجر السكر من المحاصيل الواعدة في السودان وذلك نسبة لإنتاجيته العالية من الجذور والسكر ومنتجاته كمحصول صناعي. بنجر السكر من محاصيل الطاقة البديلة الواعدة لإنتاج الإيثانول. أجريت التجربة في المزرعة التجريبية، كلية العلوم الزراعية، جامعة الجزيرة، وادمدني، السودان في الموسمين 2012/ 13 و 2013/14م على التوالي. الهدف من التجربة هو دراسة تأثير فترات الري (7 و14 و21 يوم) ومعدلات سماد النيتروفوسكا المركب (0 و100 و150 و200 كجم للهكتار) على إنتاجية الجذور والسكر لبنجر السكر (صنف بلدي) تحت ظروف الجزيرة. تم إستخدام تصميم القطع المنشقة بثلاث تكرارات. أوضحت النتائج أن تقليل فترات الري من 21 الي 14 و7 زاد قطر الجذر ووزن الجذر وإنتاجية الجذور والسكر في كلا الموسمين. زيادة معدلات سماد النيتروفوسكا المركب من 0 الى أكثر 150 كجم للهكتار حسن بشكل كبير أغلب الصفات المدروسة للجذر وإنتاجية السكر في كلا الموسمين. إعتماداً على نتائج هذه الدراسة للحصول على أعلى إنتاجية من الجذور والسكر لمحصول بنجر السكر نوصي بإضافة سماد النيتروفوسكا بمعدل 150 كجم/هكتار على أن يروى المحصول كل 7 إلى 14 يوم